Probation Officer–Probation Agency Fit: Understanding Disparities in the Use of Motivational Interviewing Techniques. Issue 1 (2nd January 2019) - Blasko, Brandy L.; Viglione, Jill; Toronjo, Heather; Taxman, Faye S.
ABSTRACT: Probation agency performance, probationer outcomes, and public safety all depend on the successful implementation of evidence-based practices (EBPs). Yet, EBP implementation is short-lived within community corrections agencies. The current study focused on interactions between 834 probation officers and their agencies (six probation jurisdictions) by examining alignment between the use of client-centered communication strategies, perceived agency support, and agency climate. Results showed a significant, negative linear relationship between probation officer-agency alignment with regard to EBPs and agency context. Quadratic regression analyses were used to model the level of the outcome (satisfaction with climate). Taken together, findings suggest agency climate is: (1) most at risk when officers are more comfortable with use of client-centered communication than they feel the agency can support, and (2) not influenced by officers uncomfortable with use client-centered communication who perceive the agency supports their use. Failure to recognize these officer differences can complicate effective implementation of EBPs in community supervision agencies. New avenues for implementation research are discussed.